2023
DOI: 10.1111/ejh.14030
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra versus etoposide‐based therapy added to high‐dose steroids for the treatment of secondary hemophagocytic lymphohistiocytosis

Benjamin J. Lee,
Yen Cao,
Pongthep Vittayawacharin
et al.

Abstract: Objective Hemophagocytic lymphohistiocytosis (HLH) is a rare life‐threatening, hyperinflammatory syndrome usually treated with high‐dose steroids (HDS), often complemented with adjunct therapies, such as etoposide (HLH‐94 protocol). Anakinra has been reported to effectively treat HLH; however, has not been comparatively examined with etoposide‐based therapies. We sought to evaluate the effectiveness and durability of these treatment approaches. Methods We performed a retrospective analysis of all adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“… 14 In adult patients receiving the HLH-94 protocol, 1-year OS rates are dismal ranging between 29% and 35%. 2 , 15 , 16 In addition, the high cumulative exposure to etoposide from the HLH-94 protocol has been implicated in significantly increasing the risk of secondary hematologic malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 14 In adult patients receiving the HLH-94 protocol, 1-year OS rates are dismal ranging between 29% and 35%. 2 , 15 , 16 In addition, the high cumulative exposure to etoposide from the HLH-94 protocol has been implicated in significantly increasing the risk of secondary hematologic malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings of anakinra use for HLH management have suggested therapeutic benefit in adult patients. 2 5 Collectively, treatment response from a pooled analysis of four studies was 78.3% ( n = 36/46) with 1-year OS reported as 33.3% ( n = 9) and 77.8% ( n = 6) from two studies. 2 5 With a median follow-up of 10 months, Bavarez et al also reported an OS of 88.2% in their subset of adult patients ( n = 18) who received anakinra (one patient with prior etoposide treatment was excluded).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this agent was approved for the treatment of rheumatologic disorders, promising data from off-label use in adults and children have brought it forward into the recommended treatment options in HLH/MAS per the consensus of the Histiocyte Society [55]. Retrospective studies using anakinra in secondary HLH are very encouraging with overall response rates as high as 80-90% [56,57]. In addition, case series have alluded to its efficacy in IEC-HS in patients treated with CD19 CAR-T products for pediatric B-ALL, DLBCL and mantle cell lymphoma [58,59].…”
Section: Interleukin-1 (Il-1) Targeting Agentmentioning
confidence: 99%